AI Shield: Protecting Business Data from Cybercrime - Anggi Ariska Putri; Aswar, Muhammad Asrul (Prosiding Seminar Nasional Ilmu Manajemen, Ekonomi, Keuangan dan Bisnis, 2023)
This research discusses the application of Artificial Intelligence (AI) in strengthening company data security in collaboration with Firewall systems, Intrusion Detection Systems (IDS), and Cryptography. With the involvement of AI which has algorithmic capabilities and predictive analysis, this qualitative descriptive research provides proactive solutions to security threats, increases detection efficiency and strengthens data security systems. These three systems make it easy to limit illegal network access, detect and encrypt data through coding. These findings have important implications in facing the ever-growing challenges of cyber crime on information security, and provide a strong foundation for a particular company or organization to maintain the integrity and confidentiality of its data.